Religious orders and personal and group attitudes and values - Wright, Beryl (Rhodes University, Faculty of Humanities, Department of Sociology and Social Work, 1970)
From Introduction: For many years I have been interested in the relationship between ethical and moral attitudes and values and religious belief. I became aware of a conflict in attitudes concerning the role of the Church in society as a member of the Methodist Church, and this stimulated me to study seriously the role of the Church in present day society. I found that members of the Wesley Guild, of which I myself was a member, conceived of the Guild in three forms: (a) as a social club; (b) as an institution for training in Christian service, both at the level of spiritual belief and practice and at the level of practical help to those in human need; (c) as an assooiation where individual spiritual values are fostered. Members differed in their view of the Guild, some seeing it in terms of all three enumerated forms, others emphasising one or two of these forms. This induced tension within the Guild. Wider observation led me to the view that this diffused concept of the Church and its functions was not peculiar to the Wesley Guild. It seemed to be general to the South African Church. I became confirmed in this view when, as a student at Rhodes University, I found that many theological students of different denominations shared it.
Keywords: Church and social problems -- South Africa; Christians -- South Africa -- Grahamstown -- Attitudes